2000
DOI: 10.1681/asn.v113403
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Expression of Dystroglycans Is Reduced in Minimal Change Nephrosis But Not in Focal Segmental Glomerulosclerosis

Abstract: Abstract. Extensive flattening of podocyte foot processes and increased permeability of the glomerular capillary filter are the major pathologic features of minimal change nephrosis (MCN) and focal segmental glomerulosclerosis (FSGS). Adhesion proteins anchor and stabilize podocytes on the glomerular basement membrane (GBM), and presumably are involved in the pathogenesis of foot process flattening. Thus far, α3 β1-integrin was localized to basal cell membrane domains. In this report, α- and β-dystroglycan (DG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…[12] Podocyte detachment is critically related to a3b1 integrin or dystrolglycan in the glomerular basement membrane. [13,14] A decreasing number of podocytes is a consequence of a lack of appropriate proliferation after podocyte injury. [15] General measures for the treatment of collapsing FSGS include blood pressure control, minimization of proteinuria by angiotensin inhibition, and lipid-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Podocyte detachment is critically related to a3b1 integrin or dystrolglycan in the glomerular basement membrane. [13,14] A decreasing number of podocytes is a consequence of a lack of appropriate proliferation after podocyte injury. [15] General measures for the treatment of collapsing FSGS include blood pressure control, minimization of proteinuria by angiotensin inhibition, and lipid-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Podocyte apoptosis results from elevated transforming growth factor-β, angiotensin II, reactive oxygen species, and reduced levels of cyclin-dependent kinase inhibitors p21 and p27 [12] . Podocyte detachment is critically related to α3β1 integrin or dystrolglycan in the glomerular basement membrane [13,14] . A decreasing number of podocytes is a consequence of a lack of appropriate proliferation after podocyte injury [15] …”
Section: Discussionmentioning
confidence: 99%
“…In brief, tissue samples were fixed in 4% formaldehyde and 0.1% distilled glutaraldehyde (Merck, Darmstadt, Germany) in 100 mM phosphate buffer (pH 7.2) for 6 to 12 hours at 4°C. Samples were soaked in sucrose, frozen, and stored in liquid nitrogen until processing for indirect immunogold labeling, as described earlier …”
Section: Methodsmentioning
confidence: 99%
“…Studies about the role of DG in glomerulopathies are ambiguous. A decreased concentration of alpha and beta dystroglycan has been described in patients with MCD in comparison with the normal level in cases with FSGS [ 44 ]. The expression of β-chain DG in the podocytes did not differ in MCD and FSGS and, moreover, the presence of β-chain DG in podocytes did not influence the steroid sensitivity [ 45 ].…”
Section: Biomarkers Potentially Contributed To Podocyte Injury or Cel...mentioning
confidence: 99%
“…The expression of β-chain DG in the podocytes did not differ in MCD and FSGS and, moreover, the presence of β-chain DG in podocytes did not influence the steroid sensitivity [ 45 ]. On the other hand, Giannico et al observed increased DG expression in renal biopsies in patients with FSGS [ 44 , 109 ].…”
Section: Biomarkers Potentially Contributed To Podocyte Injury or Cel...mentioning
confidence: 99%